2022
DOI: 10.1007/s10530-021-02720-3
|View full text |Cite
|
Sign up to set email alerts
|

Alien vs. predator: influence of environmental variability and predation on the survival of ascidian recruits of a native and alien species

Abstract: Drivers of successful introduction of exotic species remain a major headline in marine invasion biology. We ran two experiments aiming to assess factors influencing recruits' survival of one native and one alien ascidian species. A feeding experiment allowed us to monitor microscale variation of generalist fish predation, which varied significantly within a marina. We also monitored the in-situ survival of lab-grown ascidians at three locations within the marina, half with predator cage exclusion. The survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…Data from two publications using the same study locations as here was compiled. Pollutants that significantly varied between locations in Gauff et al (2022) for 2019 and all detected pollutants in Kenworthy et al (2018) for 2016 are indicated. Values below the detection limits are indicated for 2016 (with their detection limit).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Data from two publications using the same study locations as here was compiled. Pollutants that significantly varied between locations in Gauff et al (2022) for 2019 and all detected pollutants in Kenworthy et al (2018) for 2016 are indicated. Values below the detection limits are indicated for 2016 (with their detection limit).…”
Section: Discussionmentioning
confidence: 93%
“…The observed differences between these communities might be related to ambient pollution, since pollution levels measured in sediments of the inner location were often higher compared to the entrance (Tab. 1; Kenworthy et al 2018b, Gauff et al 2022). While differences between the entrance and inner communities appeared to be conserved, their differences with respect to the community settled in the middle of the marina were much more variable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations